2009
DOI: 10.1073/pnas.0908149106
|View full text |Cite
|
Sign up to set email alerts
|

Immunopurification of Ago1 miRNPs selects for a distinct class of microRNA targets

Abstract: microRNAs comprise a few percent of animal genes and have been recognized as important regulators of a diverse range of biological processes. Understanding the biological functions of miRNAs requires effective means to identify their targets. Combined efforts from computational prediction, miRNA over-expression or depletion, and biochemical purification have identified thousands of potential miRNA-target pairs in cells and organisms. Complementarity to the miRNA seed sequence appears to be a common principle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 39 publications
3
44
1
Order By: Relevance
“…1A). This is consistent with the finding of Hong et al (2009) of no enrichment for GU pairing or mismatches in RIP-chip data.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…1A). This is consistent with the finding of Hong et al (2009) of no enrichment for GU pairing or mismatches in RIP-chip data.…”
Section: Resultssupporting
confidence: 82%
“…Two recent studies (Hausser et al 2009;Hong et al 2009) have compared miRNA target features determined from such expression analyses with the results of Argonaute immunopurification (RIP-chip) experiments, and noted differences in the target features. For example, in contrast to earlier studies which have found that 39 UTR length is increased in miRNA targets, these studies found that a distinguishing feature of miRNP binding was short 39 UTR length.…”
Section: Introductionmentioning
confidence: 99%
“…We found 1,115 transcripts upregulated in AGO1 knockdown cells (see Table S6 in the supplemental material). In order to verify some of the targets, we compared the transcripts to the data sets available from Hong et al (76), and 256 transcripts had been de- scribed to be AGO1 targets. Next, we were interested in whether we had also detected these 1,115 transcripts in our decapped RNAseq libraries of XRN1 knockdown cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to its simplicity and robustness, this method has since been employed to determine the RNA targets of more than one hundred RBPs in mammalian cells, fl ies, worms, trypanosomes, and in yeast [a comprehensive list of RBP experiments is given in (28) ]. It was also the fi rst technique that was applied for the experimental exploration of miRNA targets through immunopurifi cation of Ago proteins and other miRISC proteins from human cells (29 -36) , fl ies (37,38) , and worms (39,40) . Of note, RIP allows concomitant identifi cation of the protein components of RNPs and other associated regulatory proteins by mass-spectrometry (MS) (41) .…”
Section: Ribonomics -Global Methods For the Identifi Cation Of Rna-prmentioning
confidence: 99%